Acoustic Similarity of Inner and Outer Circle Varieties of Child-Produced English Vowels. - Coy, André; Watson, Stefan (Journal of Speech, Language & Hearing Research, 2020)
Purpose: This article compares acoustic data of normally developing children from two dominant and one nondominant variety of English in order to determine phonetic proximity. Method: The study focuses on one variety of American English (AE), one British English (BE) variety, and one Jamaican English (JE) variety owing to the historical and sociopolitical influences of both dominant varieties on JE. The work examines the four corner vowels (/a/, /ɑ/, /u:/, and /i:/) of the specified varieties. Speech from children aged 8-11 years was processed to extract duration, intensity, and fundamental frequency as well as the first three formants (F1, F2, and F3) of each vowel. Results: Analysis of the acoustic variables showed, for the first time, that child-produced JE is phonetically closer to the variety of BE studied, than it is to the American variety. The acoustic properties of the child-produced JE vowels were found to be similar to those of adultproduced vowels, suggesting that, as has been shown for adult speech, there appears to be a limited impact of AE on JE. Conclusions: This is the first acoustic study of children's speech to show that, despite the proximity to BE, the Jamaican variety is clearly a distinct variety of English. As the first study comparing AE, BE, and JE, the article provides experimental evidence of the acoustic differences in the varieties and points to the implications for automatic speech recognition and educational applications for children who speak JE.